Influence of the Nonvolatile Fraction on the Sensory Perception of 40% (v/v) Ethanol‐Containing French Grape Brandies. Issue 1 (7th February 2014) - Fiches, G.; Deleris, I.; Saint‐Eve, A.; Passot, S.; Brunerie, P.; Souchon, I.
Abstract Several studies performed on wines have shown that nonvolatile and matrix components can have an impact on sensory perception through physicochemical and/or sensory interactions. In distilled spirits and as for many other food products, relationships between these components and the sensory perception are still misunderstood. In the present study, we investigated the impact of nonvolatile components on the sensory perception of two 40% (v/v) ethanol‐containing French grape brandies with different compositions and sensory qualities. For this purpose, a reconstitution strategy involving freeze‐drying was developed to test the contributions of nonvolatile components to the sensory perception of brandies. The studied products contained different levels of nonvolatile components, and corresponding to extremes values of the nonvolatile components concentration range usually found in French grape brandies. Sensory results highlighted no significant sensory difference between the two reconstituted brandies. To validate results, sensory evaluations were also performed on model beverages and revealed that sugar and phenols at contents of between 5–25 g/L and 200–1, 000 mg/L, respectively, did not have an impact on sensory perception. It could therefore be hypothesized that physicochemical and sensory mechanisms involving ethanol, which is present in very large amounts in distilled beverages, can influence physicochemical interactions and sensory perception, and reduce the impact of nonvolatile components on final sensory perception. Practical Applications This study reaffirmed the importance of aromatic perception to the global sensory image of brandies: perception differences between French grape brandies seemed to be mainly due to differences in their volatile composition. This composition depends on aroma compound formation and selection steps in the global production process of the product, such as fermentation and distillation. Product characteristics, especially their 40% v/v ethanol content, can modify sensory perception and possibly hide the effects of some nonvolatile components. The latter are known to highly contribute to the sensory profile of alcoholic drinks with lower ethanol content such as wine. This study also highlighted an interesting strategy to test the role of each sensory component on overall sensory perception and to draw conclusions about the perception complexity of beverages such as brandies.